Resonant Properties of Circular Optical Nanoantennas of Homogeneous Disks (Bulletin of Pure and Applied Sciences – Physics, 2020)
We have studied the resonant properties of circular optical nanoantennas as well as  other shapes of optical antennas without requiring any fitting parameters. This  allows for a deeper insight into scaling behavior and do faster further research since  a desired simple tool is now available to design such nanoantennas. The theory has  been applied to design antennas supporting various resonances at predefined  frequencies to respond to the desire to have multi resonant antennas for  applications. Raman sensors are extremely broad band resonators. Such circular  patch nanoantennas consist in tailoring the dispersion relation and the complex  reflection coefficient at will by carefully selecting a particular stack of layers. We  have made to characterize the resonance behavior of the potentially simplest optical  nanoantennas which is also called nanowire antennas. The nanowire as a plasmonic  cavity, a resonance occurs when the phase accumulated on a single round trip  amounts to multiple of 2π . This phase is determined by the propagation constant of  the plasmonic mode supported by the nanowire and an additional phase on  reflection at the wire termination. By fitting many resonance positions with different  nanowire lengths, the phase change on reflection is determined. Such results are  obtained only for a few simplified geometries. Nanoantennas are made from an  arbitrary stack of homogeneous disks. Increasing the radius of a single disk toward  infinitely and increasing its thickness yielded the reflection coefficient of surface  Plasmon polariton propagating along a single metallic interface at a planar  termination. The obtained results were in good agreement with previous results.